Revision of the Palaearctic and Oriental species of the genus Naarda Walker, 1866 (Lepidoptera, Erebidae, Hypeninae). Part 3. Description of three new species from Asia - Balázs Tóth; Laslo Ronkay (Nota Lepidopterologica, 2014)
We revise the Naarda egrettoides species-group and describe and illustrate three new Naarda species: N. ardeola sp. n. (Thailand), N. egrettoides sp. n. (Thailand) and N. pocstamasi sp. n. (Vietnam).